The effect of dillenia philippinensis rolfe. (Katmon) fruit extract in theblood sugar level of the albino mice. - Ignacio, Ma. Ellaine G. (2013)
Three (3) kilograms of Dillenia philippinensis rolfe. (katmon) fruits were collected from Mt. Palay-palay. Its fruit extract were given orally at the dose level of 50mg/kg to forty-five (45) albino mice for a period of two weeks. Before and after the administration of varying concentrations (25%, 50%, 75% and 100%) of Dillenia fruit extract a drop of blood was collected from the lateral saphenous vein of the mice and was tested for its sugar level by using a random blood sugar test. A non-parametric and parametric test was used to compare the blood glucose level of the albino mice before and after the administration of Dillenia fruit extract. And it showed that even though there is an increase in the blood sugar level of the albino mice treated with varying concentration of Dillenia fruit extract only the control group exhibited a significant increase with its calculated tratio of 2.97 (p<0.05) and w-ratio of 42.5. And for further analysis, one-way ANOVA and Post-hoc Analysis (Tukey method) was used. The results showed that there were no significant differences among the concentrations of Dillenia fruit extract in terms of its effectiveness in lowering or increasing the blood glucose level of albino mice.